Postconflict third-party affiliation in Canis lupus: do wolves share similarities with the great apes? - Palagi E.; Cordoni G. (Animal Behaviour, 2009)
Unsolicited third-party affiliation is defined as the first postconflict affinitive contact directed by bystanders to victims. To date, it has been found in apes and children but not in monkeys. We investigated the occurrence of unsolicited postconflict third-party affiliation in wolves, Canis lupus, and verified some functional hypotheses using a comparison with solicited contacts. Unsolicited affiliations were more frequent between individuals sharing good relationships and were reciprocated between partners (victims and third parties), thus suggesting the reciprocal nature of this mechanism (mutualistic behaviour). At an immediate level, in wolves unsolicited contacts provided benefits to the victim by breaking off aggression and restoring victims' social cohesiveness. The incidence of unsolicited interactions was affected by the presence of previous reconciliation. This result mirrors what has been found for the great apes, in which consolation may function as a partial alternative to reconciliation. Even though the cognitive skills at the basis of conflict resolution in canids still have to be investigated in detail, our study shows an unexpected similarity between wolves and the great apes. © 2009 The Association for the Study of Animal Behaviour.